2001
DOI: 10.1021/ie001090j
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Desulfurization Process for Fuel Oils Based on the Formation and Subsequent Precipitation of S-Alkylsulfonium Salts. 3. Denitrogenation Behavior of Light Oil Feedstocks

Abstract: The denitrogenation behavior of light oils, when occurring during a novel desulfurization process based on alkylation and a subsequent precipitation method, using the alkylating agents (CH3I and AgBF4), has been investigated. Denitrogenation results, obtained for three model nitrogen compounds (aniline, indole, and carbazole) in a xylene solution, were compared with the results for three light oils, of differing nitrogen, sulfur, and aromatic concentration. The nitrogen compounds in the light oils were found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(56 citation statements)
references
References 15 publications
(67 reference statements)
10
46
0
Order By: Relevance
“…Their possible core structures are indole, carbazole, acridine, and their derivatives (see Figure e). Literature studies show that indole, carbazole, and their derivatives are difficult to be removed by HDN for their basicity lower than basic nitrogen species, such as quinoline. Although acridine belongs to basic nitrogen species, hydrodeoxygenation (HDO) of N 1 O 1 (DBE of 12) may contribute to its high content in hydrotreated shale oil.…”
Section: Resultsmentioning
confidence: 99%
“…Their possible core structures are indole, carbazole, acridine, and their derivatives (see Figure e). Literature studies show that indole, carbazole, and their derivatives are difficult to be removed by HDN for their basicity lower than basic nitrogen species, such as quinoline. Although acridine belongs to basic nitrogen species, hydrodeoxygenation (HDO) of N 1 O 1 (DBE of 12) may contribute to its high content in hydrotreated shale oil.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen compounds are then precipitated as N-methylated tetrafluoroborates. Denitrogenation of light oils and vacuum gas oil was successfully achieved by this method (Table ), and it was accompanied by alkylation of sulfur and aromatics. , Studies with model compounds revealed that aniline, pyridine, quinoline, and carbazole were removed as precipitates of their corresponding methylated products, while indole and pyrrole were removed as insoluble polymerized materials. In addition, denitrogenation of basic nitrogen compounds and compounds containing alkyl substituents was more effective than that of nonbasic nitrogen compounds.…”
Section: Chemical Conversion Followed By Separationmentioning
confidence: 99%
“…In addition, denitrogenation of basic nitrogen compounds and compounds containing alkyl substituents was more effective than that of nonbasic nitrogen compounds. This is because denitrogenation by this method depends on the electron density on the nitrogen atom, which is increased by alkyl substituents …”
Section: Chemical Conversion Followed By Separationmentioning
confidence: 99%
See 2 more Smart Citations